2018
DOI: 10.1016/j.jtho.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Resected NSCLC: Effect on Postoperative Outcomes

Abstract: Sarcopenia as determined using preoperative computed tomography could be used to predict postoperative major complication and prognosis in patients with resected NSCLC. Our results may provide some important information for preoperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 41 publications
7
105
0
1
Order By: Relevance
“…Patients with WL > 10% have a significantly lower survival than those with less pronounced WL [29]. Our results confirm few recent studies reporting the negative impact of low muscle mass on survival of operated lung cancers [10,30]. Low muscle mass was mostly observed in underweight and normal weight patients (66% and 39% respectively), less frequently in overweight (21%), and rarely in obese patients (9.5%).…”
Section: Lower Bmi Weight Loss and Low Muscle Mass Negatively Impactsupporting
confidence: 85%
“…Patients with WL > 10% have a significantly lower survival than those with less pronounced WL [29]. Our results confirm few recent studies reporting the negative impact of low muscle mass on survival of operated lung cancers [10,30]. Low muscle mass was mostly observed in underweight and normal weight patients (66% and 39% respectively), less frequently in overweight (21%), and rarely in obese patients (9.5%).…”
Section: Lower Bmi Weight Loss and Low Muscle Mass Negatively Impactsupporting
confidence: 85%
“…Sarcopenia is the loss of muscle mass and function. Some reports have defined sarcopenia using the psoas muscle index (PMI) calculated from CT imaging at the level of the third lumbar vertebra . However, there is no agreed cutoff value that defines sarcopenia, with authors of the reports each establishing their own definition.…”
Section: Methodsmentioning
confidence: 99%
“…2 Although there is growing interest regarding the deleterious effects of sarcopenia on tolerance to chemotherapy and prognosis, data specifically related to lung cancer patients is lacking. The prevalence of sarcopenia is reported to occur in lung cancer patients at a range of 46-79% [3][4][5][6][7][8][9][10] and is likely dependent on age, smoking habits, 9 duration of the disease, different body mass index (BMI) 11 and gender. 4,8,10,12 To our knowledge only a few papers have investigated the clinical consequences of sarcopenia in patients with lung cancer but the results are have not been homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of sarcopenia is reported to occur in lung cancer patients at a range of 46-79% [3][4][5][6][7][8][9][10] and is likely dependent on age, smoking habits, 9 duration of the disease, different body mass index (BMI) 11 and gender. 4,8,10,12 To our knowledge only a few papers have investigated the clinical consequences of sarcopenia in patients with lung cancer but the results are have not been homogeneous. [5][6][7][8]13,14 Regarding the prognostic value of skeletal muscle radiodensity (SMD), only one study by Sjoblom et al showed that SMD had a statistically significant negative prognostic value in non-small cell lung cancer (NSCLC) patients, 15 a finding also reported in other types of tumors.…”
Section: Introductionmentioning
confidence: 99%